The Influence of Intellectual Capital (IC) And Profit–Sharing Ratio on the Return on Equity (ROE) of Indonesian Islamic Banks - Calantha Evelyn Radivie; Muljaningsih, Sri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The Islamic banking industry in Indonesia has grown significantly, particularly following the 2021 merger that established Bank Syariah Indonesia (BSI). However, the level of profitability, as measured by Return on Equity (ROE), remains less than optimal. Within the framework of Financial Intermediation Theory and Maqashid Shariah, financial performance in Islamic banks is influenced not only by conventional financial indicators but also by intangible assets such as Intellectual Capital (IC) and the application of profit- sharing financing systems. This study aims to analyze the effect of IC and Profit-Sharing Ratio on ROE in 13 Islamic Commercial Banks in Indonesia during the 2021–2024 period. The research applies a quantitative approach using multiple linear regression analysis on secondary data from annual financial reports. IC is measured using the VAIC™ method, while the Profit-Sharing Ratio is calculated from mudharabah and musyarakah financing contracts. The findings show that both IC and the Profit-Sharing Ratio significantly affect ROE, both partially and simultaneously. These results emphasize the strategic role of intellectual capital management and profit-sharing mechanisms in enhancing the profitability and sustainability of Islamic banking. This study contributes to the development of Islamic finance literature and offers practical implications for managerial decision-making in the Islamic banking sector.